SCRAMBLING INDEX DARI GRAF JARING LABA-LABA: SCRAMBLING INDEX DARI GRAF JARING LABA-LABA - Nurul Maulida Surbakti (Deli Sains Informatika, 2022)
Scrambling index of primitive graph G, denoted by K(G), is the smallest integer k such that for every pair of vertices u and v of G there exist vertex w such that there exist walks of length k that are connecting vertices u and w of G and vertices v and w of G. In this research, we discuss the scrambling index of primitive graph G consisting of s cycles where each cycle has even length and k arcs that connect each vertex in s cycless with one vertex in  the cycle. For each pair of primitive graph , we find a  formula for scrambling index that depends on s and k. Keywords: primitive graph;, spider web; scrambling index